Pulmonary sarcoidosis with a diffuse ground glass pattern on the chest radiograph. Issue 8 (August 1994) - Tazi, A; Desfemmes-Baleyte, T; Soler, P; Valeyre, D; Hance, A J; Battesti, J P
Abstract : BACKGROUND--Several chest radiographic abnormalities have been described in pulmonary sarcoidosis, but a diffuse ground glass pattern is extremely rare. METHODS--The chest radiographs of more than 1600 patients with sarcoidosis evaluated in our service between 1976 and 1991 were reviewed to determine the prevalence of this pattern on chest radiography at presentation, and to assess the clinical characteristics of these patients. RESULTS--Ten patients (0.6%) were identified with diffuse ground glass abnormalities on the chest radiography (eight men); all had associated hilar or mediastinal adenopathy. All patients were white and nine were smokers or former smokers. Nine patients were symptomatic and six had inspiratory crackles on physical examination. As a group these patients were remarkable for the frequency and severity of physiological abnormalities and the presence of various findings typically associated with "active" disease. Nine patients were followed for more than three years. All were treated with oral corticosteroids because of significant symptoms or physiological abnormalities, or both. Symptoms and radiological abnormalities disappeared or improved in all patients, but recurred in a high proportion when steroids were tapered or discontinued. By December 1992 only three patients had been withdrawn from treatment. CONCLUSIONS--A diffuse ground glass pattern on the chest radiograph is unusual in patients with sarcoidosis and may occur more commonly in white subjects and cigarette smokers. Its presence suggests the existence of active disease of recent onset likely to require long term treatment with corticosteroids.